Interleukin-6 and Depressive Mood Symptoms: Mediators of the Association Between Childhood Abuse and Cognitive Performance in Middle-Aged Adults. Issue 1 (19th March 2018) - Davis, Mary C; Lemery-Chalfant, Kathryn; Yeung, Ellen WanHeung; Luecken, Linda J; Zautra, Alex J; Irwin, Michael R
Abstract : People exposed to abuse in childhood showed cognitive deficits in middle-age, due in part to their elevated levels of inflammation and depressed mood. Abstract: Background: Childhood abuse is a risk factor for the development of cognitive deficits in adulthood, a relation that is likely mediated by stress-sensitive psychological and physiological indicators. Purpose: To evaluate whether the link between exposure to childhood abuse and cognitive function in middle adulthood is mediated by interleukin-6 (IL-6), metabolic risk, and depressive mood symptoms. Methods: Participants were 770 adults aged 40–65 recruited from the community, who completed the following: (i) a questionnaire assessing exposure to abuse prior to age 18, (ii) a phone interview assessing current depressive mood symptoms, and (iii) a home visit that included blood sampling for evaluation of IL-6 and assessment of metabolic risk indices. A follow-up telephone assessment evaluating cognitive function was completed by 555 of the participants. Structural equation modeling was used to test study hypotheses. Results: Childhood abuse predicted higher levels of IL-6, depressive mood symptoms, and metabolic risk scores ( p < .05). The relation between childhood abuse and poorer cognitive performance was mediated by IL-6 ( p = .046) and depressive mood symptoms ( p = .023), but not metabolic risk. IL-6 and depressive mood symptoms significantly mediated the relation between childhood abuse and adult cognitive function. Conclusions: Exposure to early abuse conveys enduring physiological and psychological effects, which may contribute to cognitive deficits that are evident by middle adulthood. Increased vulnerability for cognitive decline among adults with a history of early trauma and the mediating roles of IL-6 and depressive mood symptoms point to the potential value of interventions that address inflammation or depression, singly or together, to prevent cognitive decline in this at-risk population.